1997
DOI: 10.1006/viro.1997.8523
|View full text |Cite
|
Sign up to set email alerts
|

The Human Cytomegalovirus UL97 Protein Is Phosphorylated and a Component of Virions

Abstract: The expression of the human cytomegalovirus (HCMV) UL97 open reading frame in infected or transfected cells in the presence of the antiherpes compound ganciclovir (GCV) results in the intracellular phosphorylation of GCV. There are conventional kinase domains within the UL97-encoded protein (pUL97). However, the role of pUL97 in the HCMV replication cycle, and the mechanism by which it causes phosphorylation of GCV, are currently unknown. Herein, the biosynthesis and biogenesis of pUL97 was studied in HCMV-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 50 publications
5
57
0
Order By: Relevance
“…Interestingly, the antibody readily detected vPK in purified virions. Structural analysis of purified virions of other herpesviruses, including HSV, CMV, EBV, and rhesus rhadinovirus, indicate that the conserved protein kinases of these viruses are also incorporated into mature virus particles (2,12,37,50,52). This finding suggests that this kinase may play a role in phosphorylating viral proteins during virion assembly and/or regulate the functions of viral and cellular proteins upon entry into host cells and during the early stage of de novo infection (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the antibody readily detected vPK in purified virions. Structural analysis of purified virions of other herpesviruses, including HSV, CMV, EBV, and rhesus rhadinovirus, indicate that the conserved protein kinases of these viruses are also incorporated into mature virus particles (2,12,37,50,52). This finding suggests that this kinase may play a role in phosphorylating viral proteins during virion assembly and/or regulate the functions of viral and cellular proteins upon entry into host cells and during the early stage of de novo infection (47).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies on members of each of the three major groups of herpesviruses have identified a wide array of viral and cellular protein substrates of the conserved viral protein kinases. Structural analysis of purified virions of several herpesviruses, including HSV, CMV, and EBV, indicate that these protein kinases are asso-ciated with virus particles (2,12,37,50,52); thus, the kinases are in a position to influence virion assembly and events that take place after entry of the virion into the cell. A number of studies using kinase-null viral mutants demonstrated the importance of the kinase for regulating viral gene expression, replication, tissue tropism, or infection in animal models (7,11,26,35,41,48).…”
mentioning
confidence: 99%
“…Although there is growing evidence that pUL97 is an autophosphorylating protein kinase, it directs phosphorylation of the nucleoside analogue GCV (He et al, 1997 ;van Zeijl et al, 1997). We wanted to define segments of the protein involved in phosphorylation of either GCV or pUL97.…”
Section: Regions Involved In the Phosphorylation Of Gcvmentioning
confidence: 99%
“…It has been shown that pUL97 can partially substitute the function of the herpes simplex virus UL13 gene (Ng et al, 1996) and, furthermore, that after expression in the heterologous baculovirus system, the protein autophosphorylates serines and threonines (He et al, 1997). Recently, it has been published that pUL97 is also present in the virus particles and that it is posttranslationally modified by phosphorylation in HCMV-infected cells (van Zeijl et al, 1997). To get further insight into the still unknown biological function of pUL97, we first wanted to determine the functional domains of this viral protein.…”
Section: Introductionmentioning
confidence: 99%
“…A number of publications have demonstrated that pUL97 accumulates in the nucleus of HCMV-infected or transiently transfected cells (Michel et al, 1996;van Zeijl et al, 1997;Marschall et al, 2003;Prichard et al, 2005;Romaker et al, 2006;Milbradt et al, 2009;Rechter et al, 2009). Using immunofluorescence analysis of pUL97-GFP fusion constructs, it was postulated that a nuclear localization signal (NLS) exists in the N terminus of pUL97, located between amino acids 48 and 110 (Michel et al, 1998).…”
Section: Introductionmentioning
confidence: 99%